EGO DEFENSE MECHANISM OF THE CHARACTERS KAKEK GARIN AND AKU IN THE SHORT STORY ANTHOLOGY ROBOHNYA SURAU KAMI BY A.A. NAVIS - Muhammad Rafly Winanto; Roch Widjatini; Nila Mega Marahayu (Fakultas Bahasa dan Sastra Indonesia Universitas Jenderal Soedirman, 2022)
Abstract this study discusses the pshycological problems experienced by humans when they are facing a problem in their activities. On the basis of these problems, researches conducted research with the aim of describing Id, Ego, Super Ego, and Ego defense mechanism on character Kakek Garin at “Robohnya Surau Kami” and character Aku at “Angin Dari Gunung”. Then this study was analyzed using Sigmon Freud’s psychoanalytic theory to describe Id, Ego, and Super Ego, and Ego defense mechanism on character Kakek Garin at “Robohnya Surau Kami” and character Aku at “Angin Dari Gunung”. The results of this study reveal that the two characters have different Id, Ego, and Super Ego as well as different Ego defense mechanism. Kakek Garin with all the psychological conflicts he experienced finally ended his life by committing suicide, while the character Aku with all his psychological conflicts was able to survive. The results of this study also show that the two characters provide meaning about life lessons about defending yourself when you are experiencing psychological conflicts with yourself.